Witnessing and Experiencing Discrimination: A Study in Spanish Adolescents - Lorena Valdivieso-León; Alba Ayuso-Lanchares; Clara Gonzalez-Sanguino (Education Sciences, 2024)
Objectives: to examine the nature and context of discriminatory experiences among adolescents in Spain. Methods: A mixed study of discourse content analysis in 1000 randomly selected Spanish adolescents aged 12 to 16 years stratified by age, gender and territorial distribution. Data were analyzed to identify perpetrators, actions, and locations of discrimination. Results: Overall, 66% of adolescents reported witnessing or experiencing discrimination, primarily manifested through teasing, insults, and harassment. Peers were identified as the main perpetrators (73.9%), with schools being the primary context (69.4%) where discrimination occurs. Discrimination often lacked clear reasons (27.78%), but ethnicity (23.83%) and physical appearance (22.51%) were the most common factors, followed by gender (5.99%) or academic/ability issues (5.99%) or having an illness or developmental disorder (5.41%). Conclusions: Discrimination among adolescents is frequent, with racism and rejection of minority groups as the main causes. The findings underscore the need for interventions to address discriminatory behaviors in schools and broader society, with implications for adolescent well-being and mental health.